SKETSA HISTORIS POSISI KITAB KUNING DALAM LEGISLASI HUKUM ISLAM DI INDONESIA - Nur Qomari; Roihanah Roihanah (JURNAL PUSAKA, 2016)
Kitab kunings have significant influence on positive law in Indonesia, especially those with Syafi’ite school. Since the 13th century, in the beginning of the Syafi'ite school tradition come to Nusantara, the position of the kitab kunings had fluctuated until the final third of the 20th century, in which this tradition is absorbed into positive law in KHI. However, only private law that is politically acceptable in the Indonesian legal system. The Islamic criminal law, since the colonial period, could not be reserved well. Being codified in KHI, the influence of the kitab kunings, indirectly, be a source of law and the legal basis for the determination by the judge in the Religious court Keywords: kitab kuning, syafi’iyyah, law, Indonesia